CRITERIA AFFECTING CUSTOMERS’ CHOICE: THE CASE OF REZEKNE CITY CATERING COMPANIES - Litavniece, Lienīte; Silicka, Inese; Dembovska, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Increase of the number of catering businesses is driven by the growing demand, since more and more people choose eating outside. This is encouraged both by the rising welfare level and by a shift of the paradigm manifesting the diner as a place to socialize. However, from the perspective of the company, it is important to identify the main reasons why customers choose a particular eating-place. The aim of the paper is to explore the criteria influencing customers' choice and to test these criteria applying them to Rezekne city catering companies. As a result, it has been concluded that there are many criteria reviewed in the theoretical literature that could help a company to determine the criteria influencing the customers' choice. The paper is written within the framework of the RTA scientific grant "Quality Assessment of Rezekne City Catering Companies". Within the grant project, an expert questionnaire had been developed to carry out a quality assessment of Rezekne city catering enterprises. Consequently, the authors had an interest to explore the reasons motivating customers to choose a particular Rezekne city catering company according five criteria: location, offer, quality of food and drinks, company's image, and staff. As a result, the authors conclude that the most important criteria among the respondents was the quality of food and drink, as well as the offer, though, the evaluation varies depending on the particular company's specifics. The main research methods are monography, logically constructive, graphic, sociological.